Evaluating Adaptive Assessment Models for Children with Special Needs in Christian Religious Education: A Mephibosheth-Inspired Hermeneutical Framework - Novalyn Olly Tuegeh; Dicky Welly Kansil; Gilbert Timothy Majesty (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2026)
The evaluation of adaptive assessment models for children with special needs within Christian Religious Education (CRE) presents unique pedagogical and theological challenges. Standardized assessments often fail to accommodate diverse cognitive, emotional, and physical abilities, inadvertently excluding these learners from meaningful spiritual evaluation. This article proposes a constructive and hermeneutical method to develop an alternative evaluative framework inspired by the biblical narrative of Mephibosheth (2 Samuel 9). Constructively, the study synthesizes principles from special education specifically Universal Design for Learning (UDL) and differentiated assessment with a theological anthropology grounded in imago Dei. Hermeneutically, the Mephibosheth narrative is reinterpreted not as a passive recipient of charity but as a paradigmatic figure whose